'UMVM AL-BALWA: KONSEP, KEDUDUKAN DAN PEMAKAIANNYA DALAM PENENTUAN HUKUM DALAM BIDANG FIQH MUAMALAT - Abdullah, Atikullah (Jurnal Syariah, 2019)
The islamic recognition on the implementation of 'umum al-balwii concept shows that fiqh is very realistic, responsive and flexible. 'Umum al-balwii has been widely implemented in determining several hukum (laws) involving several domains in fiqh namely'ibiidah, mu'iimalah, muniikal;ah dan jiniiyah. This article focuses on the concept and roles played by 'umum al-balwa in muamalah.